FROM ALIENATION TO CONNECTEDNESS: A POSTMODERN ECOCRITICAL READING OF JOHN STEINBECK'S THE WINTER OF OUR DISCONTENT - Ashraf Kouta; Engy Saleh (European Scientific Journal, ESJ, 2013)
Within a postmodern ecocritical framework, the present paper seeks to examine John Steinbeck's ecocentric vision in his last novel The Winter of Our Discontent (1961). The paper analyzes the novel from an ecocritical perspective, showing how man's connectedness with nature highlights postmodern phenomena of identity crisis, disintegration, alienation, and deterioration of ethics. Within this framework, nature asserts itself as man's 'place,' companion, solace, and refuge from a rapidly changing American society during the 1950s and 1960s in which the heavy grip of capitalism and consumerism was felt. The paper argues that The Winter of Our Discontent foregrounds the concept of interdependence that governs the relationship between human beings and the environment, thus emphasizing Steinbeck's ecocentric vision that destabilizes the dichotomous notion that man is superior to nature. Here, the ontological landscape of a man searching for a lost disintegrated identity and escaping from moral degeneration expands within a typical postmodern literary text to form one ontological structure of which nature is a crucial component. The paper aims at finding links between postmodernism and ecocriticism, demonstrating that the protagonist's attempt to accomplish connectedness with nature is an impact of the postmodern sense of alienation, identity crisis, and the erosion of moral codes.